The effect of engagement in an HIV/AIDS integrated health programme on plasma HIV‐1 RNA suppression among HIV‐positive people who use illicit drugs: a marginal structural modelling analysis. Issue 8 (19th March 2017) - Ti, L; Dong, H; Kerr, T; Turje, RB; Parashar, S; Min, JE; Montaner, J; Wood, E; Milloy, M‐J
Abstract : Objectives: HIV treatment‐as‐prevention campaigns emphasize early diagnosis and immediate access to care and antiretroviral therapy for HIV‐positive individuals in order to increase levels of plasma HIV RNA viral load (VL) suppression. However, the possible role of harm reduction‐based programmes in this objective has not yet been well evaluated. The objective of the study was to examine the relationship between being a client of the Dr. Peter Centre (DPC; an HIV/AIDS‐focused adult integrated health programme) and VL suppression among highly active antiretroviral therapy (HAART)‐exposed HIV‐positive people who use illicit drugs (PWUD) in Vancouver, Canada. Methods: Data were derived from the AIDS Care Cohort to Evaluate Exposure to Survival Services (ACCESS) study, a study of a community‐recruited cohort of HIV‐positive PWUD. A marginal structural model using inverse probability of treatment weights was used to estimate the longitudinal relationship between being a DPC client and exhibiting a VL < 50 HIV‐1 RNA copies/mL plasma. Results: Between 2005 and 2014, 746 HAART‐exposed participants were included in the study, of whom 269 (36.1%) reported being a DPC client at some time during the study period. A marginal structural model estimated a 1.54 greater odds of achieving VL suppression (95% confidence interval 1.20–1.99) among DPC clients. Conclusions: Our findings demonstrate that participating in an innovative HIV/AIDS‐focused adult integrated health programme that provides a broad range of clinical, harm reduction, and support services may contribute to optimizing the benefits of HAART in terms of morbidity, mortality and viral transmission among PWUD, and as a result help to fulfill the goals of the treatment‐as‐prevention strategy.